PELUANG DAN TANTANGAN METAVERSE SEBAGAI MEDIA PEMBELAJARAN PAI: SEBUAH SINTESIS LITERATUR - Rahmi, Yulia; Sesmiarni, Zulfani; Azzahra, Oriza Sativa; M, Iswantir (Pendas : Jurnal Ilmiah Pendidikan Dasar, 2026)
The advancement of information and communication technology has revolutionized education, particularly Islamic Religious Education (PAI), through the metaverse as an immersive virtual space integrating virtual reality, augmented reality, and social interaction. This study synthesizes recent literature to map the opportunities and challenges of the metaverse as a PAI learning medium, addressing the gap in systematic analysis that remains partial in prior studies. Employing a qualitative descriptive approach with thematic literature synthesis methods, content and thematic analysis were applied to categorize findings from pedagogical, technological, spiritual, technical, and ethical-spiritual perspectives. The synthesis reveals transformative opportunities: pedagogically, through authentic virtual Hajj simulations that enhance student engagement; technologically, via VR/AR and AI for inclusive accessibility in remote areas; and spiritually, by strengthening the internalization of Islamic values through profound emotional experiences. However, challenges include infrastructure disparities (internet access, device costs), low teacher literacy (52% adaptation difficulties), digital distractions, and ethical risks such as the loss of worship authenticity and deviations from Sharia principles. The discussion emphasizes gradual integration based on an Islamic ethical framework, blended ADDIE training, and national regulations to ensure the metaverse enriches humanistic learning aligned with noble character. This research offers conceptual contributions for PAI teachers and policymakers, recommending hybrid development that prioritizes student equity and faith in the digital era.